Developmental toxicity assessment of common excipients using a stem cell-based in vitro morphogenesis model. (November 2017) - Yuan, Chloe J.; Marikawa, Yusuke
Abstract: Various chemical compounds can inflict developmental toxicity when sufficiently high concentrations are exposed to embryos at the critical stages of development. Excipients, such as coloring agents and preservatives, are pharmacologically inactive ingredients that are included in various medications, foods, and cosmetics. However, concentrations that may adversely affect embryo development are largely unknown for most excipients. Here, the lowest observed adverse effect level (LOAEL) to inflict developmental toxicity was assessed for three coloring agents (allura red, brilliant blue, and tartrazine) and three preservatives (butylated hydroxyanisole, metabisulfite, and methylparaben). Adverse impact of a compound exposure was determined using the stem cell-based in vitro morphogenesis model, in which three-dimensional cell aggregates, or embryoid bodies (EBs), recapitulate embryonic processes of body axis elongation and patterning. LOAEL to impair EB morphogenesis was 200 μM for methylparaben, 400 μM for butylated hydroxyanisole, 600 μM for allura red and brilliant blue, and 1000 μM for metabisulfite. Gene expression analyses of excipient-treated EBs revealed that butylated hydroxyanisole and methylparaben significantly altered profiles of developmental regulators involved in axial elongation and patterning of the body. The present study may provide a novel in vitro approach to investigate potential developmental toxicity of common excipients with mechanistic insights. Highlights: In vitro morphogenesis model is used to assess developmental toxicity of excipients. 6 common excipients, namely 3 coloring agents and 3 preservatives, are evaluated. Methylparaben and butylated hydroxyanisole disturbed morphogenesis most potently. Gene expression profiles are altered by methylparaben and butylated hydroxyanisole. More studies are needed to determine LOAEL of developmental toxicity for excipients.